2020
DOI: 10.1002/ajmg.c.31849
|View full text |Cite
|
Sign up to set email alerts
|

Human recombinant lysosomal β‐Hexosaminidases produced in Pichia pastoris efficiently reduced lipid accumulation in Tay‐Sachs fibroblasts

Abstract: GM2 gangliosidosis, Tay-Sachs and Sandhoff diseases, are lysosomal storage disorders characterized by the lysosomal accumulation of GM2 gangliosides. This accumulation is due to deficiency in the activity of the β-hexosaminidases Hex-A or Hex-B, which are dimeric hydrolases formed by αβ or ββ subunits, respectively. These disorders show similar clinical manifestations that range from mild systemic symptoms to neurological damage and premature death. There is still no effective therapy for GM2 gangliosidoses, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
(109 reference statements)
0
1
0
Order By: Relevance
“…Importantly, these results show for the first time that the eukaryotic Man 3 GlcNAc 2 N -glycan synthesized by glyco-engineered E. coli cells can mediate the uptake of a recombinant protein. Our observations agree with previous reports of lysosomal enzymes produced in hosts that synthesize N -glycans with terminal mannoses, such as α-galactosidase A ( P. pastoris , [ 69 ]), lysosomal acid lipase ( P. pastoris , [ 11 , 12 ]), iduronate-2-sulfate sulfatase ( P. pastoris , [ 13 ]), GALNS ( P. pastoris , [ 14 , 15 ]), ( P. pastoris , β-hexosaminidases [ 16 , 17 ]), glucocerebrosidase (carrot cells, [ 66 ]), and acid α-glucosidase (rice, [ 65 ]). Nevertheless, it is important to highlight that proteins produced in these hosts have about 8–12 mannose residues [ 12 , 18 , 65 , 70 ] whereas the glyco-engineered E. coli strain used here synthesizes a simpler trimannosyl N -glycan [ 29 ], which appears to be sufficient for promoting protein uptake.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, these results show for the first time that the eukaryotic Man 3 GlcNAc 2 N -glycan synthesized by glyco-engineered E. coli cells can mediate the uptake of a recombinant protein. Our observations agree with previous reports of lysosomal enzymes produced in hosts that synthesize N -glycans with terminal mannoses, such as α-galactosidase A ( P. pastoris , [ 69 ]), lysosomal acid lipase ( P. pastoris , [ 11 , 12 ]), iduronate-2-sulfate sulfatase ( P. pastoris , [ 13 ]), GALNS ( P. pastoris , [ 14 , 15 ]), ( P. pastoris , β-hexosaminidases [ 16 , 17 ]), glucocerebrosidase (carrot cells, [ 66 ]), and acid α-glucosidase (rice, [ 65 ]). Nevertheless, it is important to highlight that proteins produced in these hosts have about 8–12 mannose residues [ 12 , 18 , 65 , 70 ] whereas the glyco-engineered E. coli strain used here synthesizes a simpler trimannosyl N -glycan [ 29 ], which appears to be sufficient for promoting protein uptake.…”
Section: Resultsmentioning
confidence: 99%
“…An increasing number of studies have shown the possibility of producing active and therapeutic forms of lysosomal proteins in microorganisms [ [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] ]. This may enable the production of recombinant proteins with a reduced production cost, as well as improved stability, pharmacodynamics, and pharmacokinetic profiles [ 10 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…After administration of the α-glucosidase produced from Y. lipolytica to Pompe disease model mice, glycogen accumulation in the heart was reduced. In addition to the above examples, the production of lysosomal enzymes using the methylotrophic yeast Pichia pastoris has been reported (61,62).…”
Section: F-1 Production Of Recombinant Lysosomal Enzymes By Sugar Cha...mentioning
confidence: 99%
“…Human recombinant NAGLU (hrNAGLU) was produced in the yeast Komagataella phaffii (previously known as Pichia pastoris), following previously reported procedures. [51][52][53][54][55] Briefly, K. phaffii GS115 strain was transformed with the plasmid pPICZαAÀ NAGLU, and zeocinresistant PCR-positive clones were selected for production of the recombinant enzyme. hrNAGLU was purified from the culture medium by affinity chromatography.…”
Section: Recombinant Naglu Productionmentioning
confidence: 99%